2000
DOI: 10.1002/14651858.cd002113
|View full text |Cite
|
Sign up to set email alerts
|

Prompted voiding for the management of urinary incontinence in adults

Abstract: Background Prompted voiding is a behavioural therapy used mainly in North American nursing homes. It aims to improve bladder control for people with or without dementia using verbal prompts and positive reinforcement. Objectives To assess the e ects of prompted voiding for the management of urinary incontinence in adults. Search methods We searched the Cochrane Incontinence Group Specialised Trials Register (searched 31 January 2006) and reference lists of relevant articles. We contacted investigators in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
97
0
4

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(107 citation statements)
references
References 32 publications
2
97
0
4
Order By: Relevance
“…Bowel or bladder incontinence is thought to be preventable and reversible in the nursing home residents [152]. Instituting prompted voiding was found to be effective in reducing daytime incontinence [153][154].…”
Section: Incontinencementioning
confidence: 99%
“…Bowel or bladder incontinence is thought to be preventable and reversible in the nursing home residents [152]. Instituting prompted voiding was found to be effective in reducing daytime incontinence [153][154].…”
Section: Incontinencementioning
confidence: 99%
“…A meta-study of systematic reviews of behavioural interventions has called for clarity in the theory underpinning the use of behavioural interventions for UI. 53,54 Systematic reviews of the effectiveness of single behavioural interventions already exist for BT; 25 TV; 26 PV; 27 HT 28 and PFMT. 29 As urge strategies have been shown to be effective in stress urinary incontinence (SUI) 32 and stress strategies in urge urinary incontinence (UUI), 33 a number of trials have tested CBIs for both SUI and UUI, on the premise that combining techniques may be more effective than single techniques.…”
Section: Description Of the Interventionmentioning
confidence: 99%
“…In the review of BT, 25 trials tended to favour BT and there was no evidence of adverse effects. The review of PV 27 found evidence of increased self-initiated voiding and decreased incontinent episodes in the short term.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations